1997
DOI: 10.1111/j.1348-0421.1997.tb01897.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Borrelia burgdorferi Sensu Lato Isolated in Far Eastern Russia

Abstract: One-hundred and fifty-seven Borrelia isolated from adult ticks, Ixodes persulcatus, and wild rodents, Clethrionomys rufocanus and Apodemus peninsulae, in the far eastern part of Russia were charaeterized and identified by restriction fragment length polymorphism (RFLP) of the 5S-23S rRNA intergenic spacer. Some isolates showed unique RFLP patterns and were determined as Borrelia garinii on the basis of a sequence analysis of the intergenic spacer amplicon and reactivity with species-specific monoclonal antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
1
22
0
1
Order By: Relevance
“…Some juvenile ticks of I. persulcatus, a northern species associated with Lyme disease borreliae, were detected in some birds examined. This species has not been found previously at this survey site by flagging vegetation (unpublished data) but is known to be widely distributed in mountainous areas over 1,000 m above sea level in the eastern part of Fukui Prefecture (7,8 (16,29). Nakao et al (24) reported that isolates from bird-derived larvae of I. persulcatus were identified as ribotype II of B. garinii, the common subtype in Europe and far-eastern Asia, and most strains such as those of ribotype II generated pattern B on the 5S-23S rRNA intergenic spacer PCR-RFLP system (T. Masuzawa, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Some juvenile ticks of I. persulcatus, a northern species associated with Lyme disease borreliae, were detected in some birds examined. This species has not been found previously at this survey site by flagging vegetation (unpublished data) but is known to be widely distributed in mountainous areas over 1,000 m above sea level in the eastern part of Fukui Prefecture (7,8 (16,29). Nakao et al (24) reported that isolates from bird-derived larvae of I. persulcatus were identified as ribotype II of B. garinii, the common subtype in Europe and far-eastern Asia, and most strains such as those of ribotype II generated pattern B on the 5S-23S rRNA intergenic spacer PCR-RFLP system (T. Masuzawa, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…garinii is highly polymorphic and comprises six OspA serotypes and different ribotypes (6,14,33). Recent evidence indicates that some Asian strains of B. garinii thrive in rodent hosts rather than in avian hosts (34,36). Furthermore, recent studies suggest that OspA serotype 4 strains are associated with rodents rather than with birds (14,16).…”
Section: Discussionmentioning
confidence: 99%
“…Under the umbrella of the wider taxon Borrelia burgdorferi sensu lato, the bacteria constitute a group of 11 named genospecies, which were delineated based on DNA-DNA hybridization and sequence divergence of selected loci (2,32,34,39,40). In Europe, six genospecies are recorded as infecting Ixodes ricinus ticks (8,15,25), and the most prevalent genospecies are B. afzelii, B. garinii, and B. valaisiana (13,25).…”
mentioning
confidence: 99%
“…The remaining five cultures were cultures of multiple Borrelia isolates from ticks and rodents that were infected with two or more Borrelia species. Cultures of multiple Borrelia isolates were frequently found in surveys conducted in far eastern Russia (11,18) and northeastern China (9). The Lyme Borrelia species found in our survey areas seem to resemble those isolated from I. persulcatus collected in Hokkaido, Japan (16), in far eastern Russia (11,18), and in northeastern China (16).…”
Section: Discussionmentioning
confidence: 99%